Initial conditions for turbulent mixing simulations - Kaman, T.; Glimm, J.; Sharp, D.H. (Condensed Matter Physics, 2010)
In the context of the classical Rayleigh-Taylor hydrodynamical instability, we examine the much debated question of models for initial conditions and the possible influence of unrecorded long wave length contributions to the instability growth rate α. У контексті класичної гідродинамічної нестійкості Релея - Тейлора вивчено дискусійне питання моделей для початкових умов і можливий вплив незафіксованих далекосяжних вкладів на швидкість росту нестійкості альфа.